Empirical Evidence of the Effectiveness of Digital Gamification-Based Small Games on the Attractiveness of Physical Education Learning - laila fitria; Imam; Rajip Rusdiyanto (Media Ilmu Keolahragaan Indonesia, 2025)
This systematic review aims to evaluate empirical evidence on the effectiveness of integrating small-sided games with digital gamification in enhancing the appeal of Physical Education-learning. A Systematic Literature Review (SLR) following PRISMA guidelines was applied to ten selected empirical articles from indexed databases spanning 2015-2025. The results of the analysis show a positive convergence between the two approaches. Digital gamification, through elements such as points, badges, leaderboards, and progress bars, successfully transforms small-sided game activities into a series of structured challenges. This transformation significantly boosts students' intrinsic and extrinsic motivation, learning engagement, as well as the duration and intensity of physical activity. Furthermore, this integration creates a holistic synergy: beyond optimizing physical goals, it also strengthens socio-affective dimensions by utilizing small-sided games as a vehicle for developing cooperation, sportsmanship, and communication. The success of implementation heavily relies on careful pedagogical design, which balances competitive (performance-oriented) elements with mastery-oriented ones to ensure inclusivity and avoid excessive pressure. Practical implications emphasize the importance of teacher training and the use of gamification data for formative assessment. Further research with rigorous experimental designs, larger and more diverse samples, and long-term outcome measurements is needed to strengthen the findings and refine implementation guidelines.